The Influence of Promotion and Content Marketing on Competitive Advantages on Beauty SMEs in the Pandemic Era - Dara Safira Ramadhita; Yulia Nur Hasanah (Almana : Jurnal Manajemen dan Bisnis, 2022)
Pandemic over the past two years caused a stalemate of promotion in MSMEs, especially in SMEs beauty in Indonesia. In the end, SMEs must start better promotion methods including using Promotion through Content Marketing to be able to market products through their excellence. This research aims to analyze the influence of promotion and content marketing on the competitive advantages of SMEs beauty in the pandemic era. This research includes a type of quantitative research. This research method uses associative and causal methods. The population in this study was everyone who had already purchased products from By Lashes. The sampling technique used is Non-Probability with Purposive Sampling. The questionnaire was distributed to 100 respondents. This study uses descriptive analysis. Based on the results of research using SPSS. Through the results of this research, it can be concluded that there is a positive and significant influence of Promotion and Content Marketing on the Competitive Advantages of Beauty SMEs in the Pandemic Era. Keywords: